Electrodeposition of reduced graphene oxide with chitosan based on the coordination deposition method - Liu, Mingyang; Chen, Yanjun; Qin, Chaoran; Zhang, Zheng; Ma, Shuai; Cai, Xiuru; Li, Xueqian; Wang, Yifeng (Beilstein Journal of Nanotechnology, 2018)
The electrodeposition of graphene has drawn considerable attention due to its appealing applications for sensors, supercapacitors and lithium-ion batteries. However, there are still some limitations in the current electrodeposition methods for graphene. Here, we present a novel electrodeposition method for the direct deposition of reduced graphene oxide (rGO) with chitosan. In this method, a 2-hydroxypropyltrimethylammonium chloride-based chitosan-modified rGO material was prepared. This material disperses homogenously in the chitosan solution, forming a deposition solution with good dispersion stability. Subsequently, the modified rGO material was deposited on an electrode through codeposition with chitosan, based on the coordination deposition method. After electrodeposition, the homogeneous, deposited rGO/chitosan films can be generated on copper or silver electrodes or substrates. The electrodeposition method allows for the convenient and controlled creation of rGO/chitosan nanocomposite coatings and films of different shapes and thickness. It also introduces a new method of creating films, as they can be peeled completely from the electrodes. Moreover, this method allows for a rGO/chitosan film to be deposited directly onto an electrode, which can then be used for electrochemical detection.
Keywords: chitosan; coordination; electrodeposition; nanocomposite films; reduced graphene oxide